Changing trends in Uropathogens and their Antimicrobial sensitivity pattern (Bangladesh Journal of Medical Microbiology, 2010)
In order to monitor changes in the etiologic bacterial agents and as well as antimicrobial resistance of urinary pathogens between five years period and over several years, urinary culture and sensitivity result of patients attending the outpatient departments of Bangabandhu Sheikh Mujib Medical University (BSMMU) in 2003 and in 2008 were analyzed retrospectively. In 2003 and 2008, 668 and 715 cultures respectively were reviewed. The frequency of Escherichia coli dropped significantly in the outpatient clinics from 60.02% to 51.75%. The frequency of Klebsiella spp increased considerably. The frequency of Enterobacter spp. Enterococci spp and Acenatobacter collectively increased from 25.15 to 31.04 (p